What do our users experience? - Wilson, F (Bodleian Libraries, University of Oxford, 2022)
As library staff, we experience our spaces (physical and virtual), services and resources very differently to the way our users experience them. In this session you will gain insight into how their experiences are different to ours. Be prepared to be active, this is a fully participative session.